Simulating Déjà Vu: What happens to game performance when controlling for situational features?. (February 2016) - Jackson, Duncan J.R.; Kim, Sahangsoon; Lee, Choonwoo; Choi, Youngjun; Song, Jihee
Abstract: Video games offer a unique and flexible virtual environment in which to study human performance in response to virtual situational characteristics. In an experimental design, participants in the current study were presented with two conditions in an action video game environment. In Condition 1, the same virtual situation was presented on three occasions. In Condition 2, three different virtual situations were presented. Results revealed that person × situation interactions were of a notable magnitude, regardless as to whether the same or different situations were presented to participants, suggesting the presence of intraindividual effects across occasions. However, a general performance effect was only identifiable to a meaningful extent when different situations were presented (i.e., in Condition 2 only), suggesting that the presence of different situations is necessary in order for participants to exhibit general performance variability. Highlights: We present conditions of the same versus different virtual situations. Person × situation effects occur regardless of condition. General performance effects depend on the presence of different situations.